A highly safe lithium-ion battery positive electrode sheet and a lithium-ion battery comprising the positive electrode sheet
By coating the inorganic polysilazane-polydopamine-graphene composite coating on the positive electrode of the lithium-ion battery, the copper analysis phenomenon and heat accumulation problems are solved, the rate performance and cycle life are improved, and the battery safety is significantly improved and performance.
Patent Information
- Application Number
- CN202010232726.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-03-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-03-28
AI Technical Summary
The common copper analysis phenomenon in lithium-ion batteries poses a major hidden danger to safety, and the rate performance is not ideal, the power density is low, and the risk of heat accumulation is also high.
Inorganic polysilazane-polydopamine-graphene composite coating is used to coat the surface of the positive electrode current collector, and materials such as lithium iron phosphate and lithium manganate are used in the positive electrode active material layer to form a gradient protective layer to improve conductivity and thermal conductivity.
It effectively avoids copper analysis, reduces the content of copper ions in the electrolyte, improves the safety and rate performance of the battery, extends the cycle life, and improves the high-temperature storage performance.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a highly safe lithium-ion battery positive electrode sheet and a lithium-ion battery comprising the positive electrode sheet. Background Art
[0002] With the rapid development of informatization and intelligence in modern society, as well as the increasingly serious environmental pollution and energy shortage, society has higher and higher requirements for the capacity and output power of power storage devices, and lithium-ion batteries and capacitors have become current research hotspots. Lithium-ion batteries have the advantages of high energy density and low self-discharge rate, but their rate performance is not ideal, the power density is low, and safety hazards are increasingly valued.
[0003] By disassembling lithium-ion batteries, it is found that copper precipitation is a common safety hazard of lithium-ion batteries. Traditional technology generally believes that copper precipitation only occurs on the positive electrode surface after reverse charging or over-discharge, that is, copper electrolysis and precipitation. In practice, copper is also found to be deposited on the negative electrode surface or on the diaphragm on the negative electrode side, showing a copper-brown color. This hazard poses a major concern for safety.
[0004] Unlike the large-area copper deposition on the positive electrode surface during reverse charging, the copper deposition on the negative electrode surface is not large-area, but only localized, mostly occurring at corners, edges, or dots, and also deposited on the diaphragm surface. There are two main types of copper deposition on the negative electrode surface:
[0005] The first type is caused by moisture and other reasons. It usually occurs after pre-chemicalization. If you disassemble the battery after pre-chemicalization, you can find some copper precipitation on the surface of the negative electrode. It is mainly that before pre-chemicalization, the copper element is freed in the form of ions, and returns to the negative electrode during pre-chemical charging, and is thus precipitated on the surface of the negative electrode. This phenomenon requires two conditions: high hydrogen ion concentration and high temperature. Originally, the reaction activity of copper is lower than that of hydrogen ions, so under normal circumstances, the replacement reaction of copper element and hydrogen ions will not occur. However, according to the Nernst equation, when the hydrogen ion concentration is too high and the temperature is too high, the redox potential of copper will be reduced, so that the copper of the negative electrode current collector undergoes a replacement reaction with the hydrogen ions in the electrolyte and is freed in the form of copper ions. During pre-chemicalization, if charging is carried out casually, copper ions will be deposited on the surface of the negative electrode in the form of elemental substances, which manifests as copper precipitation on the negative electrode.
[0006] The second type is caused by internal short circuit. It usually occurs in low-voltage, especially zero-voltage batteries, especially some instant zero-voltage batteries, that is, batteries with very serious internal short circuits. This type of battery has an instant internal short circuit, which causes over-discharge at a local location, resulting in local copper electrolysis into copper ions. However, this local short circuit occurs suddenly. Once the short circuit point is caused by the melting of the diaphragm, the burning of burrs, or the displacement of dust, the short circuit will be terminated or weakened. At this time, the electrolyzed copper ions cannot reach the positive electrode normally. Then, based on the principle that the charge on the negative electrode side of the battery is zero, the electrolyzed copper ions will be deposited at a local location on the surface of the negative electrode.
[0007] Therefore, how to suppress the occurrence of copper deposition in lithium-ion batteries plays an important role in improving the safety of lithium-ion batteries. Summary of the invention
[0008] The purpose of the present invention is to provide a highly safe lithium-ion battery positive electrode sheet and a lithium-ion battery comprising the positive electrode sheet, which has the characteristics of effectively avoiding copper precipitation, avoiding heat accumulation, excellent rate performance and good cycle life.
[0009] The present invention can be implemented by the following technical solutions:
[0010] The invention discloses a highly safe lithium-ion battery positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer attached to the positive and negative surfaces of the positive electrode collector, the surface of the positive electrode collector is coated with an inorganic polysilazane-polydopamine-graphene composite coating, and the positive electrode active material layer is coated on the surface of the inorganic polysilazane-polydopamine-graphene composite coating.
[0011] Furthermore, in the inorganic polysilazane-polydopamine-graphene composite coating, the mass ratio of inorganic polysilazane, polydopamine and graphene is 50-100:1-3:1-3.
[0012] Further, the inorganic polysilazane-polydopamine-graphene composite coating is prepared by the following method:
[0013] S1. Preparation of polydopamine dispersion: using water / ethanol as a dispersion solvent, polydopamine is fully dissolved in the water / ethanol solvent by a solution oxidation method to obtain a polydopamine dispersion;
[0014] S2. Preparation of polydopamine-graphene dispersion: adding triethylamine as a stabilizer and modifier to the polydopamine dispersion, adding graphene, and dispersing uniformly under ultrasonic conditions to obtain a polydopamine-graphene dispersion;
[0015] S3, preparation of inorganic polysilazane-polydopamine-graphene coating: adding inorganic polysilazane to the polydopamine-graphene dispersion to fully mix, adding 1-methylpiperidine as an initiator, and sealing and stirring at 15-35° C. for 2-30 hours to polymerize the system to obtain inorganic polysilazane-polydopamine-graphene coating;
[0016] S4. Preparation of inorganic polysilazane-polydopamine-graphene coating: uniformly and continuously coating the inorganic polysilazane-polydopamine-graphene glue on the surface of the positive electrode current collector, and continuously drying it in a coating oven to form an inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector.
[0017] Furthermore, the inorganic polysilazane-polydopamine-graphene coating is coated on the positive and negative surfaces of the positive electrode current collector by multiple coatings, and the coating amount of the inorganic polysilazane-polydopamine-graphene coating formed by the multiple coatings decreases gradually, thereby forming a dense gradient protective layer on the surface of the positive electrode current collector, each layer forms a two-dimensional conductive and thermal network, and a three-dimensional conductive and thermal network is formed between the layers.
[0018] Further, the active material of the positive electrode active material layer is lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide.
[0019] Furthermore, the positive electrode current collector is a smooth or rough copper foil with a thickness of 5-16 μm, and the single-sided thickness of the inorganic polysilazane-polydopamine-graphene coating on the positive electrode current collector is 2-10 μm.
[0020] Furthermore, the average particle size D50 of the active material in the positive electrode active material layer is 1 to 20 μm, and the compaction density PD of the positive electrode active material layer is 2.0 to 4.5 g / cm 3 .
[0021] Another aspect of the present invention is to protect a lithium-ion battery, the positive electrode plate of which adopts the above-mentioned high-safety lithium-ion battery positive electrode plate.
[0022] The invention discloses a highly safe lithium-ion battery positive electrode sheet and a lithium-ion battery comprising the positive electrode sheet, which have the following beneficial effects:
[0023] First, effectively avoid copper precipitation. In the inorganic polysilazane-polydopamine-graphene coating, the three components undergo cross-linking polymerization during the coating preparation process to form a self-curing strong bonding coating sol. Graphene and inorganic polysilazane have good compatibility and corrosion resistance, and are evenly adhered to the surface of the positive electrode collector to form a protective layer on the surface of the positive electrode collector, effectively preventing the copper foil positive electrode collector from being corroded by the electrolyte, and effectively reducing the content of copper ions dissolved in the electrolyte. It avoids the copper precipitation phenomenon of overcharge and over-discharge of the positive electrode and the copper precipitation phenomenon of the negative electrode during the pre-forming process or the diaphragm piercing the internal micro-short circuit from the source, effectively improving the safety of lithium-ion batteries; the N group in the polydopamine molecule has a strong complexing ability for metal ions, and complexes the metal ions that may be dissolved from the positive electrode material during the high temperature process, reducing the free metal ions in the electrolyte, and significantly reducing the damage to the negative electrode structure caused by the reduction of metal ions on the negative electrode, which not only avoids the safety hazards of copper precipitation, but also helps to improve the high-temperature storage performance and cycle performance of the battery;
[0024] Second, the heat dissipation is good. In the inorganic polysilazane-polydopamine-graphene coating, the three components undergo cross-linking polymerization during the coating preparation process to form a self-curing strong bonding coating sol. Graphene and inorganic polysilazane form the coating skeleton, and polydopamine is evenly dispersed in the coating to form point contacts in the two-dimensional structure of the graphene layer. The advantages of graphene conductivity and the characteristics of polydopamine thermal conductivity are fully combined to form a three-dimensional thermal conductive network, avoiding heat accumulation.
[0025] Third, the rate performance is excellent. In the inorganic polysilazane-polydopamine-graphene coating, the three components undergo cross-linking polymerization during the coating preparation process to form a self-curing strong bonding coating sol. Graphene and inorganic polysilazane form a coating skeleton. Graphene has the advantages of large specific surface area and good conductivity, which avoids the inorganic polysilazane-polydopamine-graphene coating from hindering the conductivity between the positive electrode active material layer and the positive electrode current collector, effectively reducing the internal resistance of the lithium-ion battery and improving its rate performance. Polydopamine has higher compatibility with the electrolyte and is more easily wetted by the electrolyte, which greatly accelerates the electrolyte absorption rate and helps to improve the battery's rate performance and cycle performance.
[0026] Fourth, the cycle life is long. In the inorganic polysilazane-polydopamine-graphene coating, the three components undergo cross-linking polymerization during the coating preparation process. The self-curing strongly bonded coating sol has strong adhesion to the positive electrode collector and small contact internal resistance. It will not desorb between the positive electrode collector and the positive electrode active material layer even after multiple cycles of charge and discharge, effectively ensuring the cycle life of the lithium-ion battery. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0028] The invention discloses a highly safe lithium-ion battery positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer attached to the positive and negative surfaces of the positive electrode collector, the surface of the positive electrode collector is coated with an inorganic polysilazane-polydopamine-graphene composite coating, and the positive electrode active material layer is coated on the surface of the inorganic polysilazane-polydopamine-graphene composite coating.
[0029] Furthermore, in the inorganic polysilazane-polydopamine-graphene composite coating, the mass ratio of inorganic polysilazane, polydopamine and graphene is 50-100:1-3:1-3.
[0030] Further, the inorganic polysilazane-polydopamine-graphene composite coating is prepared by the following method:
[0031] S1. Preparation of polydopamine dispersion: using water / ethanol as a dispersion solvent, polydopamine is fully dissolved in the water / ethanol solvent by a solution oxidation method to obtain a polydopamine dispersion;
[0032] S2. Preparation of polydopamine-graphene dispersion: adding triethylamine as a stabilizer and modifier to the polydopamine dispersion, adding graphene, and dispersing uniformly under ultrasonic conditions to obtain a polydopamine-graphene dispersion;
[0033] S3, preparation of inorganic polysilazane-polydopamine-graphene coating: adding inorganic polysilazane to the polydopamine-graphene dispersion to fully mix, adding 1-methylpiperidine as an initiator, and sealing and stirring at 15-35° C. for 2-30 hours to polymerize the system to obtain inorganic polysilazane-polydopamine-graphene coating;
[0034] S4. Preparation of inorganic polysilazane-polydopamine-graphene coating: uniformly and continuously coating the inorganic polysilazane-polydopamine-graphene glue on the surface of the positive electrode current collector, and continuously drying it in a coating oven to form an inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector.
[0035] Furthermore, the inorganic polysilazane-polydopamine-graphene coating is coated on the positive and negative surfaces of the positive electrode current collector by multiple coatings, and the coating amount of the inorganic polysilazane-polydopamine-graphene coating formed by the multiple coatings decreases gradually.
[0036] Further, the active material of the positive electrode active material layer is lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide.
[0037] Furthermore, the positive electrode current collector is a smooth or rough copper foil with a thickness of 5-16 μm, and the single-sided thickness of the inorganic polysilazane-polydopamine-graphene coating on the positive electrode current collector is 2-10 μm.
[0038] Furthermore, the average particle size D50 of the active material in the positive electrode active material layer is 1 to 20 μm, and the compaction density PD of the positive electrode active material layer is 2.0 to 4.5 g / cm 3 .
[0039] Another aspect of the present invention is to protect a lithium-ion battery, the positive electrode plate of which adopts the above-mentioned high-safety lithium-ion battery positive electrode plate.
[0040] Example 1
[0041] The invention discloses a highly safe lithium-ion battery positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer attached to the positive and negative surfaces of the positive electrode collector, the surface of the positive electrode collector is coated with an inorganic polysilazane-polydopamine-graphene composite coating, and the positive electrode active material layer is coated on the surface of the inorganic polysilazane-polydopamine-graphene composite coating.
[0042] In this embodiment, in the inorganic polysilazane-polydopamine-graphene composite coating, the mass ratio of inorganic polysilazane, polydopamine, and graphene is 100:2:1. The inorganic polysilazane-polydopamine-graphene composite coating is prepared by the following method:
[0043] S1. Preparation of polydopamine dispersion: using water / ethanol as a dispersion solvent, polydopamine is fully dissolved in the water / ethanol solvent by a solution oxidation method to obtain a polydopamine dispersion;
[0044] S2. Preparation of polydopamine-graphene dispersion: adding triethylamine as a stabilizer and modifier to the polydopamine dispersion, adding graphene, and dispersing uniformly under ultrasonic conditions to obtain a polydopamine-graphene dispersion;
[0045] S3, preparation of inorganic polysilazane-polydopamine-graphene coating: adding inorganic polysilazane to the polydopamine-graphene dispersion to fully mix, adding 1-methylpiperidine as an initiator, and sealing and stirring at 15-35° C. for 2-30 hours to polymerize the system to obtain inorganic polysilazane-polydopamine-graphene coating;
[0046] S4. Preparation of inorganic polysilazane-polydopamine-graphene coating: uniformly and continuously coating the inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector, and continuously drying in a coating oven to form an inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector. During the coating process, the inorganic polysilazane-polydopamine-graphene coating is coated on the positive and negative surfaces of the positive electrode current collector by multiple coatings, and the amount of the inorganic polysilazane-polydopamine-graphene coating formed by multiple coatings decreases gradually.
[0047] In this embodiment, the active material of the positive electrode active material layer is lithium cobalt oxide. The average particle size D50 of the active material in the positive electrode active material layer is 1-20 μm, and the compaction density PD of the positive electrode active material layer is 3.8 g / cm 3 The positive electrode current collector is a smooth copper foil with a thickness of 6 μm, and the single-sided thickness of the inorganic polysilazane-polydopamine-graphene coating on the positive electrode current collector is 3 μm.
[0048] Example 2
[0049] The invention discloses a highly safe lithium-ion battery positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer attached to the positive and negative surfaces of the positive electrode collector, the surface of the positive electrode collector is coated with an inorganic polysilazane-polydopamine-graphene composite coating, and the positive electrode active material layer is coated on the surface of the inorganic polysilazane-polydopamine-graphene composite coating.
[0050] In this embodiment, in the inorganic polysilazane-polydopamine-graphene composite coating, the mass ratio of inorganic polysilazane, polydopamine, and graphene is 100:2:1. The inorganic polysilazane-polydopamine-graphene composite coating is prepared by the following method:
[0051] S1. Preparation of polydopamine dispersion: using water / ethanol as a dispersion solvent, polydopamine is fully dissolved in the water / ethanol solvent by a solution oxidation method to obtain a polydopamine dispersion;
[0052] S2. Preparation of polydopamine-graphene dispersion: adding triethylamine as a stabilizer and modifier to the polydopamine dispersion, adding graphene, and dispersing uniformly under ultrasonic conditions to obtain a polydopamine-graphene dispersion;
[0053] S3, preparation of inorganic polysilazane-polydopamine-graphene coating: adding inorganic polysilazane to the polydopamine-graphene dispersion to fully mix, adding 1-methylpiperidine as an initiator, and sealing and stirring at 15-35° C. for 2-30 hours to polymerize the system to obtain inorganic polysilazane-polydopamine-graphene coating;
[0054] S4. Preparation of inorganic polysilazane-polydopamine-graphene coating: uniformly and continuously coating the inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector, and continuously drying in a coating oven to form an inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector. During the coating process, the inorganic polysilazane-polydopamine-graphene coating is coated on the positive and negative surfaces of the positive electrode current collector by multiple coatings, and the amount of the inorganic polysilazane-polydopamine-graphene coating formed by multiple coatings decreases gradually.
[0055] In this embodiment, the active material of the positive electrode active material layer is lithium iron phosphate. The average particle size D50 of the active material in the positive electrode active material layer is 1-20 μm, and the compaction density PD of the positive electrode active material layer is 2.3 g / cm 3 The positive electrode current collector is a rough copper foil with a thickness of 12 μm, and the single-side thickness of the inorganic polysilazane-polydopamine-graphene coating on the positive electrode current collector is 8 μm.
[0056] Example 3
[0057] The invention discloses a highly safe lithium-ion battery positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer attached to the positive and negative surfaces of the positive electrode collector, the surface of the positive electrode collector is coated with an inorganic polysilazane-polydopamine-graphene composite coating, and the positive electrode active material layer is coated on the surface of the inorganic polysilazane-polydopamine-graphene composite coating.
[0058] In this embodiment, in the inorganic polysilazane-polydopamine-graphene composite coating, the mass ratio of inorganic polysilazane, polydopamine, and graphene is 80:1:3. The inorganic polysilazane-polydopamine-graphene composite coating is prepared by the following method:
[0059] S1. Preparation of polydopamine dispersion: using water / ethanol as a dispersion solvent, polydopamine is fully dissolved in the water / ethanol solvent by a solution oxidation method to obtain a polydopamine dispersion;
[0060] S2. Preparation of polydopamine-graphene dispersion: adding triethylamine as a stabilizer and modifier to the polydopamine dispersion, adding graphene, and dispersing uniformly under ultrasonic conditions to obtain a polydopamine-graphene dispersion;
[0061] S3, preparation of inorganic polysilazane-polydopamine-graphene coating: adding inorganic polysilazane to the polydopamine-graphene dispersion to fully mix, adding 1-methylpiperidine as an initiator, and sealing and stirring at 15-35° C. for 2-30 hours to polymerize the system to obtain inorganic polysilazane-polydopamine-graphene coating;
[0062] S4. Preparation of inorganic polysilazane-polydopamine-graphene coating: uniformly and continuously coating the inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector, and continuously drying in a coating oven to form an inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector. During the coating process, the inorganic polysilazane-polydopamine-graphene coating is coated on the positive and negative surfaces of the positive electrode current collector by multiple coatings, and the amount of the inorganic polysilazane-polydopamine-graphene coating formed by multiple coatings decreases gradually.
[0063] In this embodiment, the active material of the positive electrode active material layer is lithium manganese oxide and lithium cobalt oxide. The average particle size D50 of the active material in the positive electrode active material layer is 1-20 μm, and the compaction density PD of the positive electrode active material layer is 2.0 g / cm 3 The positive electrode current collector is a rough copper foil with a thickness of 14 μm, and the single-side thickness of the inorganic polysilazane-polydopamine-graphene coating on the positive electrode current collector is 6 μm.
[0064] Example 4
[0065] The invention discloses a highly safe lithium-ion battery positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer attached to the positive and negative surfaces of the positive electrode collector, the surface of the positive electrode collector is coated with an inorganic polysilazane-polydopamine-graphene composite coating, and the positive electrode active material layer is coated on the surface of the inorganic polysilazane-polydopamine-graphene composite coating.
[0066] In this embodiment, in the inorganic polysilazane-polydopamine-graphene composite coating, the mass ratio of inorganic polysilazane, polydopamine, and graphene is 50: 3: 2. The inorganic polysilazane-polydopamine-graphene composite coating is prepared by the following method:
[0067] S1. Preparation of polydopamine dispersion: using water / ethanol as a dispersion solvent, polydopamine is fully dissolved in the water / ethanol solvent by a solution oxidation method to obtain a polydopamine dispersion;
[0068] S2. Preparation of polydopamine-graphene dispersion: adding triethylamine as a stabilizer and modifier to the polydopamine dispersion, adding graphene, and dispersing uniformly under ultrasonic conditions to obtain a polydopamine-graphene dispersion;
[0069] S3, preparation of inorganic polysilazane-polydopamine-graphene coating: adding inorganic polysilazane to the polydopamine-graphene dispersion to fully mix, adding 1-methylpiperidine as an initiator, and sealing and stirring at 15-35° C. for 2-30 hours to polymerize the system to obtain inorganic polysilazane-polydopamine-graphene coating;
[0070] S4. Preparation of inorganic polysilazane-polydopamine-graphene coating: uniformly and continuously coating the inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector, and continuously drying in a coating oven to form an inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector. During the coating process, the inorganic polysilazane-polydopamine-graphene coating is coated on the positive and negative surfaces of the positive electrode current collector by multiple coatings, and the amount of the inorganic polysilazane-polydopamine-graphene coating formed by multiple coatings decreases gradually.
[0071] In this embodiment, the active material of the positive electrode active material layer is lithium nickel cobalt manganese oxide. The average particle size D50 of the active material in the positive electrode active material layer is 1-20 μm, and the compaction density PD of the positive electrode active material layer is 3.8 g / cm 3 The positive electrode current collector is a smooth copper foil with a thickness of 6 μm, and the single-side thickness of the inorganic polysilazane-polydopamine-graphene coating on the positive electrode current collector is 6 μm.
[0072] Comparative Example 1
[0073] The only difference between Comparative Example 1 and Example 1 is that no inorganic polysilazane is added to the inorganic polysilazane-polydopamine-graphene coating.
[0074] Comparative Example 2
[0075] The only difference between Comparative Example 2 and Example 1 is that polydopamine is not added to the inorganic polysilazane-polydopamine-graphene coating.
[0076] Comparative Example 3
[0077] The only difference between Comparative Example 3 and Example 1 is that no graphene is added to the inorganic polysilazane-polydopamine-graphene coating.
[0078] Comparative Example 4
[0079] The only difference between Comparative Example 4 and Example 1 is that the surface of the positive electrode current collector is not coated with the inorganic polysilazane-polydopamine-graphene coating.
[0080] In order to verify the technical effect of the present invention, Example 1 and Comparative Examples 1-4 were prepared into 18650 cylindrical batteries with the same capacity for relevant tests. The relevant test results are shown in Table 1:
[0081] Table 1 Performance test results
[0082] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Appearance of the negative electrode after disassembly after formation No significant changes Slowly turns to golden yellow, copper precipitation occurs No significant changes Slowly turns to golden yellow, copper precipitation occurs Rapidly turns to golden yellow. Copper precipitation phenomenon 3C discharge / 0.5C charge capacity ratio (%) 93.5 87.9 83.5 68.3 78.6 5C discharge / 0.5C charge capacity ratio (%) 88.5 68.3 65.7 38.5 63.1 1C charge and discharge 500 cycles retention rate (%) 75.8 53.6 52.1 / 48.3 GB / T-18287-2013 Short circuit test pass Not passed pass Not passed Not passed GB / T-18287-2013 Overcharge Test pass Not passed pass Not passed Not passed GB / T-18287-2013 forced discharge test pass Not passed pass Not passed Not passed GB / T-18287-2013 Mechanical shock test pass Not passed pass Not passed Not passed GB / T-18287-2013 Temperature Cycle Test pass Not passed pass Not passed Not passed
[0083] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the specification and described above. However, any technician familiar with the profession can make some changes, modifications and equivalent changes made by using the technical content disclosed above without departing from the scope of the technical solution of the present invention, which are all equivalent embodiments of the present invention. At the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A highly safe positive electrode sheet for a lithium-ion battery, comprising a positive electrode current collector and a positive electrode active material layer attached to the positive and negative surfaces of the positive electrode current collector, characterized in that: The surface of the positive electrode current collector is coated with an inorganic polysilazane-polydopamine-graphene composite coating, and the positive electrode active material layer is coated on the surface of the inorganic polysilazane-polydopamine-graphene composite coating; In the inorganic polysilazane-polydopamine-graphene composite coating, the mass ratio of the inorganic polysilazane, polydopamine and graphene is 50-100:1-3:1-3; The inorganic polysilazane-polydopamine-graphene composite coating is prepared by the following method: S1. Preparation of polydopamine dispersion: using water / ethanol as a dispersion solvent, and using a solution oxidation method to fully dissolve polydopamine in the water / ethanol solvent to obtain a polydopamine dispersion; S2. Preparation of polydopamine-graphene dispersion: adding triethylamine as a stabilizer and modifier to the polydopamine dispersion, adding graphene, and dispersing uniformly under ultrasonic conditions to obtain a polydopamine-graphene dispersion; S3, preparation of inorganic polysilazane-polydopamine-graphene coating: adding inorganic polysilazane to the polydopamine-graphene dispersion to fully mix, adding 1-methylpiperidine as an initiator, and sealing and stirring at 15-35° C. for 2-30 hours to polymerize the system to obtain inorganic polysilazane-polydopamine-graphene coating; S4, preparation of inorganic polysilazane-polydopamine-graphene coating: uniformly and continuously coating the inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector, and continuously drying in a coating oven to form an inorganic polysilazane-polydopamine-graphene coating on the surface of the positive electrode current collector; The positive electrode current collector is a smooth or rough copper foil with a thickness of 5-16 μm, and the single-side thickness of the inorganic polysilazane-polydopamine-graphene coating on the positive electrode current collector is 2-10 μm.
2. The highly safe positive electrode plate for lithium-ion batteries according to claim 1, characterized in that: The inorganic polysilazane-polydopamine-graphene coating is coated on the positive and negative surfaces of the positive electrode current collector by multiple coatings, and the coating amount of the inorganic polysilazane-polydopamine-graphene coating formed by the multiple coatings decreases gradually.
3. The high-safety lithium-ion battery positive electrode sheet according to claim 2, characterized in that: The active material of the positive electrode active material layer is lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide.
4. The highly safe positive electrode plate for lithium-ion batteries according to claim 3, characterized in that: The average particle size D50 of the active material in the positive electrode active material layer is 1 to 20 μm, and the compaction density PD of the positive electrode active material layer is 2.0 to 4.5 g / cm 3 .
5. A lithium ion battery, characterized in that: It comprises a high-safety lithium-ion battery positive electrode sheet according to any one of claims 1 to 4.
Citation Information
Patent Citations
Lithium ion battery pole piece coating having heat dissipation function
CN107492664A
Polysilazane-containing coating liquid
CN1694936A